From Uncertainties to Solutions: A Scenario-Based Framework for an Agriculture Protection Zone in Magic Valley Idaho - Daniel Cronan; E. Jamie Trammell; Andrew Kliskey (Land, 2023)
As growth in the western U.S. continues to lead to the development of land, pressure is being exerted on agricultural production, and could lead to the loss of prime agricultural land. A wide array of perspectives concerning agricultural protection requires a variety of possible solutions. Diverse and plausible scenarios, driven by stakeholders, can be modeled by researchers to guide potential solutions to address key challenges within a region. This paper addresses one stakeholder-defined social-ecological system (SES) solution in the context of southern Idaho, one of the fastest-growing states in the U.S.: agricultural protection zoning. This project demonstrates a method for incorporating an Agriculture Protection Zone (APZ) within a suite of scenarios showing land protection opportunities across a range of future conditions and challenges. The results, by way of a Geodesign framework, entail suitability analyses through a series of weighted raster overlays to analyze scenario-based solutions. The suite of scenario solutions was compared to demonstrate effective proportions of the APZ. The analysis of the results, as a solution gradient, aim to inform policy makers, planners, and developers about the efficiencies of various APZ delineations as well as a methodology to demonstrate the impact of solutions based on assumptions of stakeholder-informed future scenarios.